Enhanced TCP Westwood Slow Start Phase - Al-Hasanat, Mohanad; Seman, Kamaruzzaman; Saadan, Kamarudien (Discoveries in Agriculture and Food Sciences, 2014)
Many end-to-end TCP implementations have been presented in the past decade. Despite that they used different methods to improve transport protocols over wireless networks; they mostly shared the same original TCP principles. TCP Westwood introduced a novel end-to-end bandwidth estimation mechanism. Nevertheless, it maintains the same slow start phase presented in TCP Reno. For the initial slow start phase, there is no safe slow start threshold value. In this paper, we propose to use the bandwidth estimation to calculate the initial slow start threshold value after the second round trip time. Furthermore, we introduce a faster state in which TCP increases the transmission rate once the link is underutilizing. As a result, the new proposed method shows better performance comparing to TCP Westwood, and TCP NewReno techniques.